Clinical, Neuroimaging, and Electrographic Predictors of Phenobarbital Failure in Newborns With Hypoxic Ischemic Encephalopathy and Seizures. (July 2019) - Dwivedi, Deepak; Lin, Nan; Venkatesan, Charu; Kline-Fath, B.; Holland, Katherine; Schapiro, Mark
Background: Many neonates with hypoxic ischemic encephalopathy and seizures do not respond to the first line antiepileptic drug, phenobarbital. Little is known about what factors are associated with its failure. Objective: To examine factors associated with failure of phenobarbital therapy in neonates with hypoxic ischemic encephalopathy and seizures. Design/Methods: A single-center retrospective review of 50 term (>35 weeks) neonates with hypoxic ischemic encephalopathy and seizures treated with phenobarbital as the first-line antiepileptic. Neonates were classified into either responders (n = 30) or nonresponders (n = 20). Nonresponse was defined as continued seizures after maximum dosing of phenobarbital or an additional antiepileptic. Subjects with acceptable magnetic resonance imaging (MRI) scans obtained within 2 weeks of birth were included in the study and rated using an MRI injury scoring system. Charts were reviewed for demographic, clinical, and laboratory variables. Resuscitation and seizure scores were also calculated. Electroencephalographic (EEG) background activity was reviewed in 2 different time epochs (12-24 hours and 24-36 hours of life) and graded as per ACNS guidelines. Results: There were no significant group differences in demographic, clinical, and laboratory variables except nonresponders, who had higher mean seizure score ( P = .01) and significantly more injury on MRI scan for white matter ( P = .004), parenchymal cortex ( P = .027), and watershed ( P = .009) regions. Neonates with moderately abnormal or severely abnormal background EEG responded poorly to phenobarbital. Conclusion: In the presence of above factors, one can anticipate that additional antiepileptic medication may be needed. These data also support that larger studies should be done to look prospectively at using alternative agents first line in patients with severe injury.